INFLUENCE OF LEADERSHIP STYLES, MOTIVATION, ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE OF COMMERCIAL BANKS OF PAKISTAN - Hammad Zafar; Ambreen Abubakar; Sheikh M.Fakhre Alam Siddiqu (Policy Research Journal, 2025)
This study set out to investigate how employee performance in Pakistan's commercial banking industry was affected by organizational culture, motivation, and transformational leadership and transactional leadership. Data was gathered quantitatively through the use of a self-administered questionnaire, and the study's positivist research paradigm and survey research design were combined. A random sample of 102 responses was chosen for the study. The PLS, culminating structural and measurement model, was used to assess the data. It shows that Performance in Pakistan's commercial banking industry is not significantly impacted by either transformational or transactional leadership approaches. However, it has been demonstrated that organizational culture and motivation significantly and favorably affect performance. The study provides managers in this industry with insightful information, recommending a change in emphasis from strict leadership techniques to tactics that put an emphasis on staff motivation and a positive company culture. This is in line with the particular requirements of the industry and offers a framework for improving worker performance in unconventional ways.